2018
DOI: 10.1002/hep4.1243
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Patients Undergoing Chronic Hepatitis C Virus Treatment With Ledipasvir/Sofosbuvir

Abstract: Ledipasvir‐sofosbuvir, a once‐a‐day, oral combination pill, was approved in 2014 for the treatment of chronic hepatitis C infection. Initial trials did not comment on nephrotoxicity; however, recent data suggest a risk of acute kidney injury (AKI) with the use of the medication. We assessed the rates of AKI in patients undergoing ledipasvir‐sofosbuvir in a large, urban tertiary care center. This single‐center retrospective observation study included all patients undergoing therapy from October 1, 2014, to Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
7
1
2
Order By: Relevance
“…However, a worsening proteinuria was observed in patients with proteinuria of greater than 500 mg/d before therapy by Lubetzky et al [5] A recent study also revealed a slight decrease in GFR during the first year following the end of treatment, while the graft function remained stable over the pre-treatment year [14]. In our study, Scr was not significantly changed in most patients, except for two patients with impaired but stable renal function before therapy, who had a Scr elevation (AE grade 1) without acute rejection and recovered after treatment cessation, that was consistent with the recent study by Brown et al [15] Although doubtful, these data suggested possible association between AKI and SOF-containing DAAs administration. Furthermore, recent study on the histopathology showed acute interstitial nephritis in patients with AKI after SOF-containing antiviral therapy [16].…”
Section: Discussionsupporting
confidence: 91%
“…However, a worsening proteinuria was observed in patients with proteinuria of greater than 500 mg/d before therapy by Lubetzky et al [5] A recent study also revealed a slight decrease in GFR during the first year following the end of treatment, while the graft function remained stable over the pre-treatment year [14]. In our study, Scr was not significantly changed in most patients, except for two patients with impaired but stable renal function before therapy, who had a Scr elevation (AE grade 1) without acute rejection and recovered after treatment cessation, that was consistent with the recent study by Brown et al [15] Although doubtful, these data suggested possible association between AKI and SOF-containing DAAs administration. Furthermore, recent study on the histopathology showed acute interstitial nephritis in patients with AKI after SOF-containing antiviral therapy [16].…”
Section: Discussionsupporting
confidence: 91%
“…After approval of SOF/LDV, there were few published case reports and studies which showed new or worsening renal failure. 8,[16][17][18][19] These retrospective studies showed that acute kidney injury and worsening of baseline CKD after SOF/LDV treatment were reversible. The exact mechanism of nephrotoxicity with sofosbuvir containing DAA is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Cirrhosis was reported to be a risk factor for AKI upon HCV treatment in several studies [1,24]. In ERCHIVES cohort study, patients with baseline cirrhosis had higher risk of eGFR decrease >30 ml/min/1.73m 2 at SVR12.…”
Section: Factors On Daa Treatment To Renal Function At Svr12mentioning
confidence: 99%
“…Some studies reported that the use of DAA may resulted in acute tubular necrosis (ATN) and acute interstitial nephritis (AIN). [24] A small case series at Miami reported that the renal biopsies at SVR22 to SVR 93 for patients treated with DAA who developed unknown cause of kidney injury had AIN, and three of the eight patients had worsening CKD and progressed to kidney failure requiring hemodialysis despite high dose steroid treatment. [28] Pathological data was not obtained from our patients, but male sex, cirrhosis with higher MELD score, concurrent malignancy treatment, lower baseline eGFR (CKD3B), and hypertension with or without ACEI/ARB use could potentially attribute the risk to renal function injury that could be possibly caused by AIN/ATN.…”
Section: Factors On Daa Treatment To Renal Function At Svr12mentioning
confidence: 99%